Violence among Middle School and High School Students Analysis and Implications for Prevention. National Institute of Justice Research in Brief - Lockwood, Daniel; Department of Justice, Washington, DC. National Inst. of Justice ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1997)
Violent incidents among at-risk middle school and high school students are discussed. The type and frequency of these incidents are identified, but the focus is on factors such as the relationship among the antagonists, the sequence of events and escalations, and the goals and justifications cited by the students. Information is drawn from in-depth interviews with 110 students from public schools at which the level of violence is high. The 110 students, 86 of whom were African Americans, reported 250 incidents of violence. Data show that the problem of violence is growing, as is juveniles' risk of victimization. The design of this study was chosen to provide information that can be used in the curricula of school-based conflict resolution programs. In the largest proportion of incidents, the first step was relatively minor, but escalated. About 5% eventually involved a gun. Most incidents took place among young people who knew each other, and most incidents started in the school or the home. The most common goal was retribution, followed by an attempt to bring about compliance, and self defense or defense of one's image, and justifications offered stemmed from a value system in which violence was acceptable. In adopting the findings to violence prevention programs, reducing the frequency of opening moves may be the most promising approach. (Contains five exhibits.) (SLD)
Availability: National Criminal Justice Reference Service, P.O. Box 6000, Rockville, MD 20849-6000; telephone: 800-851-3420; e-mail: askncjrs@ncjrs.org.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Conflict Resolution; Curriculum Development; High Risk Students; High School Students; High Schools; Incidence; Intermediate Grades; Junior High Schools; Middle School Students; Middle Schools; Minority Groups; Prevention; School Safety; Values; Victims of Crime; Violence; Reports, Evaluative